2010
DOI: 10.4304/jetwi.2.4.300-309
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Prediction Accuracy n Trust-aware Collaborative Filtering Recommenders through T-index Metric and TopTrustee Lists

Abstract: The growing popularity of Social Networks raises the important issue of trust. Among many systems which have realized the impact of trust, Recommender Systems have been the most influential ones. Collaborative Fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In the present context, the higher the Tindex value of a user, the more trustworthy that user becomes. Fazeli et al showed how the T-index improves the structure of a generated trust network of users by creating connections to more trustworthy users (Fazeli et al 2010). Trust networks of users are described as a graph in which nodes represent the users and directed edges show the trust relationships (Dokoohaki and Matskin 2008;Fazeli et al 2010;Golbeck 2005).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present context, the higher the Tindex value of a user, the more trustworthy that user becomes. Fazeli et al showed how the T-index improves the structure of a generated trust network of users by creating connections to more trustworthy users (Fazeli et al 2010). Trust networks of users are described as a graph in which nodes represent the users and directed edges show the trust relationships (Dokoohaki and Matskin 2008;Fazeli et al 2010;Golbeck 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Fazeli et al showed how the T-index improves the structure of a generated trust network of users by creating connections to more trustworthy users (Fazeli et al 2010). Trust networks of users are described as a graph in which nodes represent the users and directed edges show the trust relationships (Dokoohaki and Matskin 2008;Fazeli et al 2010;Golbeck 2005). Fazeli et al created the trust relationships between users based on the ratings users gave to the items in their system (Fazeli et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations